Rancangan Teknis Dan Analisis Biaya Reklamasi Pada Area In Pit Dump X Site Pulau Pakal PT. Aneka Tambang Tbk. UBPN Maluku Utara - Hafizurahman Dwi Saputra; Rusli HAR; Mulya Gusman; Tri Gamela Saldy (Journals Mining Engineering : Bina Tambang, 2023)
PT. Antam Tbk. UBPN Maluku Utara has converted a former mining land into an in-pit dump for the disposal of low-grade cover soil and materials. If the area is already covered by cover soil, the area must be immediately reclaimed. Special treatment and attention are required in handling waste materials in the X in-pit dump area, as the waste material belongs to PAF material which has the potential to cause acid rock drainage problems. Based on the calculation, the bench width is 3.5 m, the single slope slope is 350, the height is 8 m and the backslope is 5%. Based on measurements, the area of stage 1 is 19,537.182 m2, stage 2 is 21,537.501 m2 and stage 3 is 13,086.461 m2. From the calculation of material 1volume, different results were obtained between the existing landfill plan, with the estimated regrading completion time ranging from 37 to 151 days, and for 19 days for revegetation in stage 1, stage 2 for 24 days and stage 3 for 13 days. For the check dump, the total volume is 10,565.62 m3 with a completion time of 14 days. The total reclamation cost ranges from Rp 451,223,407 to the largest Rp 35,365,018,549.